Ahli dalam Mengelola UMKM melalui Aplikasi Point of Sales - Ambarriani, Anastasia Susty; Sakti Hermawan, Bernadus Yenaldy; Gunaasih, Sang Ayu Putu Piastini (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
The purposes of this service activity are to improve financial information through the Point of Sales application, determine costs, and promote Rosaline Bolu and Cookies Tiwul partners. Rosaline Tiwul Bolu and Cookies is a micro business that sells Tiwul-based typical Jogja souvenirs such as cakes and cookies located on Jl. L. Adisucipto No. 7, Kec. Depok, Sleman Regency. The method used in this activity is divided into several stages: planning, implementation, process evaluation, and making a point of sales preparation module. Partners are expected to be able to independently enter data into the Soda Pos point of sales application. Furthermore, it is hoped that it can assist the practice of selling on marketplaces such as Shopee to expand the market share of the cookie’s products.